2021
DOI: 10.3390/catal11040492
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Butyrylcholinesterase in Starch and Gelatin Gels

Abstract: The present study demonstrates a simple approach to enhancing thermal stability of butyrylcholinesterase (BChE) by using natural polymers. Analysis of thermal inactivation of the tetrameric BChE in starch and gelatin gels at 50–64 °C showed that thermal inactivation followed second-order kinetics and involved two alternating processes of BChE inactivation, which occurred at different rates (fast and slow processes). The activation enthalpy ΔH# and the activation entropy ΔS# for BChE in starch and gelatin gels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…For instance, 3% starch gel was chosen as a carrier for producing single-use BChE preparations [84]. It was also found that BChE activity was not affected by variations in potato starch concentration in the gel within a 1-4.2% range (Figure 4).…”
Section: Characterization Of Preparations Produced By Immobilizing En...mentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, 3% starch gel was chosen as a carrier for producing single-use BChE preparations [84]. It was also found that BChE activity was not affected by variations in potato starch concentration in the gel within a 1-4.2% range (Figure 4).…”
Section: Characterization Of Preparations Produced By Immobilizing En...mentioning
confidence: 99%
“…The rehydration of such preparations (soaking in buffer solution) took a long time, thus increasing the assay duration. For similar reasons, in experiments with BChE immobilization in gelatin gel, 1.4% of gelatin was chosen as the optimal percentage [58,84].…”
Section: Characterization Of Preparations Produced By Immobilizing En...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that water-soluble polymers can change the rates of cellular processes via stabilizing biological structures. It is shown [ 1 , 2 , 3 ] that enzymes included in the gelatin or starch gel matrix become more stable and lead to an increase in the activity. Moreover, water-soluble polymers such as polyethylene glycol (PEG) may cause toxic effects on living organisms [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%